THÈME : ETUDE COMPARATIVE DES PERFORMANCES ENTRE LES ÉLÈVES INTERNES ET EXTERNES DES ÉCOLES SECONDAIRES LUKANGA, MALKIA WA MBINGU ET TUADIBISHE AUX EXAMENS D’ETAT DE 2006 À 2010 - RUHANGAZA, BAHATI (IJRDO - Journal of Social Science and Humanities Research, 2022)
Currently the education remains very important whose World has always needed to endorv useful citizens in the society. The question of the performance concerns the world, Africa, Democratic Republic of Congo, Lubero territory, Butembo Town and secondary schools in particular of Lukanga, Malkia wa Mbingu and Tuadibishe of educational province North Kivu 2. Thises being our theme : comparative study of performance between internal and external pupils of secondary schools of Lukanga, Malkia wa Mbingu and Tuadibishe at state’s examens of 2006-2010. At the way out of this analysis of the results by the comparison of average and the application of statistical test Z the conditions of life of the boarding school do not influence the performance of the state’s examens since the results for all, the test has been significant or Zo = (13,96) >Zc = (1,645) and hence the principal hypothesis has been infirmed